2019
DOI: 10.1016/j.nmni.2019.100547
|View full text |Cite
|
Sign up to set email alerts
|

Role of efflux pumps in reduced susceptibility to tigecycline in Acinetobacter baumannii

Abstract: Acinetobacter baumannii is an important human pathogen responsible for a various type of infections. These bacterial strains are generally resistant to numerous antibiotics. Therefore, eradication of such strains is problematic and related to high mortality. We investigated the effect of cyanide 3-chlorophenylhydrazone (CCCP) efflux pump inhibitor in tigecycline-resistant strains of Acinetobacter baumannii. In a cross-sectional study, from July until the end of February 2017, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 32 publications
0
27
1
Order By: Relevance
“…The results of the present study showed that the MIC for 43 of 47 tetracycline-resistant isolates (91.48%) was significantly reduced, by 4-16-fold in the presence of the efflux pump inhibitor. Similarly, Ardehali et al 27 found that CCCP reduced considerably the MIC of 51.25% of tigecycline-resistant A. baumannii isolates by 2-4-fold. The MICs of isolates resistant to minocycline, doxycycline, and tetracycline in the presence of different efflux pump inhibitors, such as CCCP, phenyl-arginine-β-naphthylamide, 1-(1-naphthylmethyl)-piperazine, reserpine, and verapamil were significantly reduced 28 .…”
Section: Discussionmentioning
confidence: 89%
“…The results of the present study showed that the MIC for 43 of 47 tetracycline-resistant isolates (91.48%) was significantly reduced, by 4-16-fold in the presence of the efflux pump inhibitor. Similarly, Ardehali et al 27 found that CCCP reduced considerably the MIC of 51.25% of tigecycline-resistant A. baumannii isolates by 2-4-fold. The MICs of isolates resistant to minocycline, doxycycline, and tetracycline in the presence of different efflux pump inhibitors, such as CCCP, phenyl-arginine-β-naphthylamide, 1-(1-naphthylmethyl)-piperazine, reserpine, and verapamil were significantly reduced 28 .…”
Section: Discussionmentioning
confidence: 89%
“…44 According to high antibiotic resistance among bacteria, in order to prevent undesirable effects of sepsis and septicemia, as well as in order to reduce the mortality rate due to these infections, precise detection and use of effective antibiotics for an efficient treatment are critical. 8,[45][46][47] Consequently, awareness of the antibiotic resistance patterns among common pathogens, holding workshops to correct prescription of empiric treatment, and changes in antimicrobial use are warranted and highly recommended. Finally, the results of DDM and MIC tests are of great importance, and individuals' free access to antibiotics should be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…are considered as the multidrug efflux pumps. In general, these efflux pumps can lead to the development of antibiotic‐resistant strains by decreasing the antibiotic concentration inside the cell [4–7]. AdeIJK , AdeABC , and AdeFGH are the most important efflux pumps known in A. baumanii , which belong to RND family [8].…”
Section: Introductionmentioning
confidence: 99%